PS-BPB02-3: TARGETING FORMYL PEPTIDE RECEPTORS AS A NOVEL APPROACH TO TREAT HYPERTENSION-INDUCED ADVERSE CARDIOVASCULAR REMODELLING AND DYSFUNCTION. (January 2023) - Singh, Jaideep; Jackson, Kristy L; Gumanti, Audrey; Fang, Haoyun; Woodman, Owen L; Ritchie, Rebecca H; Greening, David; Head, Geoffrey A; Qin, Chengxue
Abstract : Introduction: Chronic unresolved inflammation has been shown to contribute to the development and progression of hypertension-induced cardiovascular damage. Failure to resolve inflammation exacerbates the risk and severity of cardiovascular disease. Currently, available therapies have limited efficacy in treating hypertension and its associated complications. Formyl peptide receptors (FPR) play a critical role in the regulation of resolution of inflammation. We have previously discovered that a FPR small-molecule prototype Cmpd17b exerts cardioprotective and vasoprotective effects against acute and severe inflammatory cardiac insults, but its impact on a chronic inflammatory insult in cardiovascular diseases, such as hypertension, has not been explored. Aim and hypothesis: To investigate the therapeutic potential of a FPR agonist, Cmpd17b on cardiac and vascular remodelling and function, and blood pressure regulation in hypertensive mice. Methods: Male C57BL/6 mice (12 weeks old) were implanted with a radiotelemetry probe to measure MAP (mean arterial pressure). Hypertensive mice (AngII infused at 0.7 mg/kg/day, subcutaneously) and normotensive mice (saline infused, subcutaneously) underwent 24-hour blood pressure recordings via telemetry at baseline and during 4 weeks daily treatment with Cmpd17b (50 mg/kg/day, intraperioneally) or its vehicle. Sympathetic nervous system (SNS) activity was assessed using power spectral analysis. At week 4, cardiac and vascular function was assessed using B-mode and M-mode echocardiography. At the end of the study, heart and arteries were collected, cardiac and vascular remodelling (fibrosis and hypertrophy) and function, and cutting-edge comparative qualitative proteomics were assessed. Results: Cmpd17b reduced MAP, SNS activity, cardiac and vascular adverse remodelling and dysfunction in hypertensive mice (Table). Cutting-edge quantitative proteomics analysis revealed that hypertension-induced significant adverse structural remodelling (110 proteins in the heart and 60 proteins in the aorta) and mitochondrial dysregulation (38 in the heart and 91 in the aorta), consisted with function and pathology observed. Those changes were prevented by FPR agonism (53 structural cardiac proteins and 38 vascular structural proteins) and (24 cardiac mitochondrial proteins and 36 vascular mitochondrial proteins). Conclusions: Our study demonstrated for the first time that FPR prototype small-molecule Cmpd17b reduced hypertension-induced cardiovascular damage, supporting the development of FPR-based therapy to treat cardiovascular complications in systemic hypertension.